Curcumae Radix: A Review of Traditional Use, Phytochemistry, Pharmacology, Toxicology and Quality Control - Niu, Yu‐Ting; Xu, Hao‐Nan; Zhang, Yu‐Ying; Li, Xin‐Zhuo; Li, Yu‐Ze; Song, Xiao‐Mei; Zhang, Dong‐Dong; Wang, Wei (Chemistry & biodiversity, 2024)
Curcumae Radix (CuR) is a traditional Chinese medicine that has been used in China for more than 1,000 years. It has the traditional efficacy of activating blood and relieving pain, promoting qi and relieving depression, clearing heart and cooling blood, and promoting gallbladder and removing jaundice. Based on this, many domestic and foreign scholars have conducted systematic studies on its chemical composition, pharmacological effects, toxicity and quality control. Currently, 250 compounds, mainly including terpenoids and curcuminoids, have been isolated and identified from CuR, which has pharmacological activities, including antitumor, anti‐inflammatory and analgesic, antidepressant, hepatoprotective, hemostatic, hematopoietic, and treatment of diabetes mellitus. In modern clinical practice, CuR is widely used in the treatment of tumors, breast hyperplasia, hepatitis, and stroke. However, the generation of toxicity and clinical application of CuR and Caryophylli Flos, the determination of the concoction process of artifacts, the determination of specific Quality Marker, and the establishment of the quality control system of CuR, are problems that need to be solved urgently at present.